PERANAN KEPUASAN KONSUMEN DALAM MENINGKATKAN LOYALITAS KONSUMEN (SUATU SURVEY PERGURUAN TINGGI POLITEKNIK DI JAWA BARAT) - Mukaram Mukaram (Politeknik Negeri Sriwijaya, 2013)
The study used the descriptive method, this is done in the form of the analysis of primary data from questionnaire distribution. The number of respondents was 1511 students. From these 1511 are comprised of state polytechnic students numbered 540, while the rest of the amount is 971 students from private polytechnics. In this study, of 1,511 questionnaires were collected only 1346 were used in the data analysis stage. Statistical analysis used is regression analysis with SPSS program. The results of this study indicate that the level of consumer satisfaction was quite satisfied and leads to satisfied, it is reflected by the results of data analysis showed the mean number of 3.37. For Consumer loyalty variable, data analysis results show the mean number of 3.71. This figure indicates that consumer loyalty at enough level and tend to satisfied level. While regression analysis showed that consumer satisfaction contributed 0.570 to the consumer loyalty with a significance level of 0.000. As such concluded that polytechnic student satisfaction affect positive and significant effect on the polytechnic student loyalty.